Dinamika Psikologis Tokoh Utama dalam Novel Rumah Tanpa Cahaya karya Lenn Liu - Camelya Fajria; Nori Anggraini (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to comprehensively describe the psychological dynamics of Natta's character in the novel Rumah Tanpa Cahaya through the framework of Sigmund Freud's psychoanalytic theory. The main focus of the study is to analyze the structural interactions of personality including the Id, Ego, and Superego, and to identify various self defense mechanisms activated by the character due to the internal conflict he experiences. The method used is descriptive qualitative with a literary psychology approach as the main analytical basis for dissecting the hidden inner character. The results of the study indicate that Natta's character's behavior is a form of integrative struggle that demands immediate gratification (Id), rational consideration of painful reality (Ego), and strong moral pressure from the internalization of social norms (Superego). Natta's Id demands the fulfillment of basic needs for security and affection. Meanwhile, the Superego provides moral pressure that triggers disproportionate anxiety. Natta's Ego operates as a mediator that works hard to balance the drives of the Id and the demands of the Superego, which forces the Ego to activate self-defense mechanisms such as repression, rationalization, and especially sublimation. This mechanism serves as a psychic barrier to maintain her mental stability and prevent her from experiencing total collapse due to the accumulation of past trauma. Overall, this novel depicts the complexity of the human psyche in the face of existential crises and unresolved past wounds.